Electrolyzed water catalyst as well as preparation method and application thereof

By constructing the MxSy composite structure on a graphene substrate and performing plasma modification, the precise anchoring of platinum group metal single atoms is achieved by combining magnetron sputtering and chemical vapor deposition, the existing electrolytic catalysts are solved, and the efficient and low-cost electrolytic catalytic effect is achieved.

CN119753735APending Publication Date: 2025-04-04HUANENG CLEAN ENERGY RES INST +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411843300.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Existing electrolytic water catalysts cannot take into account low cost, high activity and high efficiency. Especially during the electrolysis of alkaline water, the hydrogen evolution reaction kinetics are slow, which affects the electrocatalytic efficiency.

Method used

By constructing the MxSy composite structure on a graphene substrate and performing plasma surface modification, an environment rich in active defect positions is created, and precise anchoring of platinum group metal single atoms is achieved by using magnetron sputtering method and/or chemical vapor deposition method.

Benefits of technology

The loading of platinum group metals is significantly reduced, the charge transport path is optimized, the intrinsic activity and stability of electrolytic water catalysts are improved, and high catalytic activity and low cost effects are achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119753735A_ABST
    Figure CN119753735A_ABST
Patent Text Reader

Abstract

The invention provides an electrolyzed water catalyst as well as a preparation method and application thereof. The electrolyzed water catalyst comprises graphene, MxSy and platinum group metal single atoms, and the preparation method comprises the following steps: firstly, carrying out hydrothermal reaction on raw materials of graphene and MxSy to obtain a first intermediate catalyst; and then coating a second solution containing the first intermediate catalyst on the surface of a substrate, performing plasma irradiation, and then treating by adopting a magnetron sputtering method and / or a chemical vapor deposition method to obtain the electrolyzed water catalyst. According to the invention, an MxSy composite structure is constructed on a graphene substrate, and plasma surface modification is supplemented, so that an environment rich in active defect sites is created; according to the present invention, the platinum group metal single atom can be accurately anchored through the magnetron sputtering method and / or the chemical vapor deposition method, such that the platinum group metal loading capacity is significantly reduced so as to reduce the cost, and the intrinsic activity and the stability of the water electrolysis catalyst are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of water electrolysis, and in particular to a water electrolysis catalyst, a preparation method and application thereof. Background Art

[0002] As one of the key technologies for achieving renewable energy storage and conversion, electrocatalytic water splitting has received extensive attention in recent years. Especially in the field of alkaline water electrolysis, it has become an indispensable link in the hydrogen energy industry chain due to its significant advantages such as high production process safety, stable operating conditions and excellent production efficiency. However, although the hydrogen evolution reaction (HER) in the alkaline water electrolysis process has simple reactants, it involves a multi-step electron transfer reaction with a high energy barrier, which leads to slow reaction kinetics and seriously affects the electrocatalytic efficiency.

[0003] Traditionally, platinum group metals (PGMs), such as platinum (Pt), rhodium (Rh), palladium (Pd), and iridium (Ir), are often used as catalysts for HER due to their excellent electrocatalytic activity. However, the scarcity and high prices of these metal resources have become the main bottlenecks restricting their large-scale application. Especially in the water electrolysis industry, the catalyst cost accounts for a significant proportion of the total cost, which not only increases the production cost, but also limits the sustainable development of the hydrogen energy industry.

[0004] Therefore, developing a HER catalyst with low PGM usage, low cost, high catalytic activity and high efficiency has become a technical problem that urgently needs to be solved. Summary of the invention

[0005] The main purpose of the present invention is to provide a water electrolysis catalyst, a preparation method and application thereof, so as to solve the problem that the water electrolysis catalyst in the prior art cannot have low cost, high activity and high efficiency.

[0006] In order to achieve the above object, according to one aspect of the present invention, a method for preparing a water electrolysis catalyst is provided, wherein the water electrolysis catalyst comprises graphene, M x S y and single atoms of platinum group metals, the preparation method comprises the following steps: step S1, mixing a sulfur precursor, an M-containing precursor, a structure directing agent, water and an alcohol to obtain a first solution, adding graphene oxide to the first solution, and performing a hydrothermal reaction to obtain a first intermediate catalyst; step S2, coating a second solution including the first intermediate catalyst on a substrate surface, and performing plasma irradiation to generate a second intermediate catalyst on the substrate surface to obtain an irradiated substrate; step S3, treating the irradiated substrate by a magnetron sputtering method and / or a chemical vapor deposition method to load the platinum group metal, and obtaining a water electrolysis catalyst on the substrate surface; M x S yHere, M includes one or more of Ni, Zn, Mo and Co, 1≤x≤2, 1≤y≤3; and the platinum group metal includes one or more of ruthenium, rhodium, palladium, osmium, iridium and platinum.

[0007] Further, in step S1, the sulfur precursor includes one or more of thiourea, sodium sulfide and potassium sulfide, and the molar concentration is 0.01-10 mol / L; and / or, the M-containing precursor includes anions and cations, the anions include one or more of chloride ions, sulfate ions, acetate ions and acetylacetonate ions, and the cations include M ions, and the molar concentration of the M-containing precursor is 0.01-10 mol / L; and / or, the structure directing agent includes one or more of sodium fluoride, barium chloride, ethylenediamine and cystine, and the molar concentration is 0.001-0.1 mol / L, and the pH of the first solution is controlled to be 6-8 using the structure directing agent; and / or, the alcohol includes one or more of methanol, ethanol, ethylene glycol, glycerol and isopropanol, and the volume ratio of water to alcohol is (0.1-10):1; and / or, the solid-liquid ratio of graphene oxide to the first solution is (1-50) mg:100 mL.

[0008] Furthermore, in step S1, mixing includes ultrasound and / or stirring, and the mixing temperature is 10-30°C; preferably, the frequency of ultrasound is 20-40kW, and the time is 0.5-4h; preferably, the stirring speed is 100-400rpm, and the time is 1-12h; and / or, the temperature of the hydrothermal reaction is 160-200°C, and the time is 2-10h; and / or, step S1 also includes the step of washing the first intermediate catalyst alternately 2-6 times and centrifuging it 2-6 times, and then drying it; preferably, water, ethanol, carbon disulfide, acetone and water are used for washing in sequence; preferably, the centrifugal speed is 5000-10000rpm, and the time is 0.5-5h; preferably, the drying temperature is 30-100°C, and the time is 0.5-24h.

[0009] Further, in step S2, in the second solution, the content of the first intermediate catalyst is 10-100 mg / mL; and / or, the second solution also includes one or more of methanol, ethanol, ethylene glycol, glycerol and isopropanol; and / or, the coating includes one or more of ultrasonic spraying, screen printing and spin coating; and / or, the substrate includes one or more of stainless steel plate, nickel plate, titanium plate and copper plate; and / or, after coating, the coating density of the coating on the surface of the irradiated substrate is 0.5-10 mg / cm 2 , thickness is 0.1~10μm.

[0010] Furthermore, in step S2, the power of plasma irradiation is 100-300W, the atmosphere includes inert gas and / or H2, the vacuum degree is 10-100Pa, the temperature is 25-50°C, and the time is 0.5-3h; preferably, the atmosphere includes H2 and inert gas, and the volume ratio of the two is 1:(25-100).

[0011] Furthermore, the number of vacancy defects in the second intermediate catalyst is 5 to 15 per nm. 2 .

[0012] Further, in step S3, the magnetron sputtering method includes: placing the irradiated substrate in a vacuum chamber, applying an electric field and a magnetic field in a vacuum environment to ionize the sputtering gas into gas ions, and using the gas ions to collide with a cathode target so that atoms of the cathode target escape and sputter on the surface of the irradiated substrate to load platinum group metals, wherein the cathode target is selected from ruthenium, rhodium, palladium, osmium, iridium or platinum, the distance between the cathode target and the irradiated substrate is 2 to 20 cm, the sputtering power is 10 to 100 W, the sputtering time is 5 to 30 min, the temperature of the irradiated substrate is 20 to 50 ° C, the sputtering gas is argon or helium, and the gas flow rate is 20 to 100 mL / min; and / or, the vapor deposition method includes: heating and vaporizing a platinum group metal precursor salt and delivering it into a reaction chamber through a carrier gas, wherein the platinum group metal precursor salt releases atoms on the surface of the irradiated substrate, so that the platinum group metal is deposited on the surface of the irradiated substrate, wherein the carrier gas includes one or more of oxygen, hydrogen, argon and helium, the platinum group metal precursor includes one or more of acetylacetonate of ruthenium, rhodium, palladium, osmium, iridium and platinum, the vaporization temperature of the platinum group metal precursor is 150-200°C, the temperature of the irradiated substrate is 200-300°C, the pressure is 1-100 kPa, and the deposition time is 5-120 min.

[0013] According to another aspect of the present invention, a water electrolysis catalyst obtained by the above preparation method is provided.

[0014] Furthermore, in the water electrolysis catalyst, the loading amount of the platinum group metal is 0.01 to 2 wt%, the content of graphene is 10 to 20 wt%, and the content of M x S y The content is 78-88wt%; and / or, the platinum group metal in the water electrolysis catalyst exists in the form of a single atom.

[0015] According to another aspect of the present invention, there is provided application of the above-mentioned water electrolysis catalyst in the field of water electrolysis.

[0016] By applying the technical solution of the present invention, M is constructed on a graphene substrate. x S yThe composite structure is assisted by plasma surface modification to create an environment rich in active defect sites; and then through magnetron sputtering and / or chemical vapor deposition, the precise anchoring of single atoms of platinum group metals can be achieved. The preparation method of this method not only significantly reduces the loading of platinum group metals and thus reduces costs, but also optimizes the charge transfer path at the structural level, thereby improving the intrinsic activity and stability of the water electrolysis catalyst. The water electrolysis catalyst prepared by the present invention has high catalytic activity, stable performance, and economy. When it is used in the field of water electrolysis, it has a low overpotential, high hydrogen evolution efficiency, and can operate stably for a long time. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0018] Figure 1 A schematic diagram of the preparation process of the water electrolysis catalyst according to Example 1 of the present invention is shown;

[0019] Figure 2 shows a microscopic morphology of the water electrolysis catalyst of Example 1 of the present invention at a magnification of 5000 times; and

[0020] Figure 3 The microscopic morphology of the water electrolysis catalyst of Example 1 of the present invention at a magnification of 20,000 times is shown. DETAILED DESCRIPTION

[0021] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0022] It should be noted that the terms "first", "second", etc. in the specification and claims of the present invention are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the numbers used in this way can be interchanged under appropriate circumstances to describe the embodiments of the present invention.

[0023] As described in the background of the present invention, the prior art has the problem that water electrolysis catalysts cannot take into account low cost, high activity, and high efficiency. In order to solve the above problems, in a typical embodiment of the present invention, a method for preparing a water electrolysis catalyst is provided, wherein the water electrolysis catalyst comprises graphene, M x S yand single atoms of platinum group metals, the preparation method comprises the following steps: step S1, mixing a sulfur precursor, an M-containing precursor, a structure directing agent, water and an alcohol to obtain a first solution, adding graphene oxide to the first solution, and performing a hydrothermal reaction to obtain a first intermediate catalyst; step S2, coating a second solution including the first intermediate catalyst on a substrate surface, and performing plasma irradiation to generate a second intermediate catalyst on the substrate surface to obtain an irradiated substrate; step S3, treating the irradiated substrate by a magnetron sputtering method and / or a chemical vapor deposition method to load the platinum group metal, and obtaining a water electrolysis catalyst on the substrate surface; M x S y Here, M includes one or more of Ni, Zn, Mo and Co, 1≤x≤2, 1≤y≤3; and the platinum group metal includes one or more of ruthenium, rhodium, palladium, osmium, iridium and platinum.

[0024] In step S1, M can be grown on the surface of graphene oxide (rGO) through a hydrothermal reaction. x S y Specifically, the sulfur precursor reacts with the M-containing precursor to generate M x S y At the same time, under the hydrothermal environment and the reduction effect of organic solvents, rGO is reduced to graphene GO, which can improve the conductivity of water electrolysis catalysts. 2 The surface atoms of the two-dimensional materials composed of hybrids have high surface energy, which makes graphene have strong adsorption capacity and can adsorb and stabilize catalysts (M x S y ) precursor molecules. At the same time, graphene can adjust the size, dispersion and morphology of catalyst particles through interaction with the catalyst, thereby improving the activity of the catalyst. x S y interaction to form a 2D / 2D heterojunction catalyst M x S y @GO (It should be noted that @ in this application means coating, M x S y @GO means M x S y coated on the surface of GO). x S y @GO has high conductivity and abundant active sites, which is conducive to enhancing the charge transfer ability and providing a stable substrate for the subsequent loading of single-atom platinum group metals. In this process, the structure-directing agent in the solution interacts with the reactant molecules or the crystal surface to limit the growth direction and speed of the crystal, which can effectively regulate the crystal phase and size of the composite material and promote M x S y Uniform distribution on rGO or GO.

[0025] It should be noted that this application specifically limits M x S y The type of M element and the range of x and y values ​​in the above formula can provide active sites to promote hydrogen adsorption and desorption, while the specific range of x and y can ensure the electronic structure and stability of the material, optimize the charge transfer path, and reduce the reaction energy barrier. x S y It has strong electrical conductivity and adsorption capacity. At the same time, the strong interaction between metal ions and sulfur ions can form a metal-sulfur surface structure with high catalytic activity, which can effectively promote the electrocatalytic reaction.

[0026] Step S2, by plasma irradiation coated with M x S y @GO substrate, which can remove M x S y @GO surface functional groups (such as sulfur, carbon, oxygen, etc.) optimize its surface state and form highly reactive defect sites, providing preferred anchoring positions for single-atom platinum group metals and promoting efficient deposition of single-atom platinum group metals in subsequent steps. The plasma environment can promote surface modification, reduce the binding energy of single-atom platinum group metals, and enhance the M x S y The bonding strength between @GO and single-atom platinum group metals can improve the stability and activity of water electrolysis catalysts.

[0027] Step S3, using magnetron sputtering and / or chemical vapor deposition, can deposit highly dispersed platinum group metal atoms on the substrate, which is conducive to the precise control of catalytic sites. Among them, the addition of platinum group metal atoms can enhance the intrinsic activity of water electrolysis catalysts, reduce the energy barrier of hydrogen evolution reaction (HER), and x S y The synergistic effect of nanostructured carbon and graphene can significantly improve the catalytic efficiency of HER, while greatly reducing the use of platinum group metals and effectively controlling costs.

[0028] It should be noted that, in this application, plasma treatment is used to x S y Highly reactive defect sites are formed on the surface of @GO materials, which have strong adsorption to platinum group metal atoms. Through magnetron sputtering and / or chemical vapor deposition, single atoms of platinum group metals are preferentially anchored at defect sites rather than forming agglomerated nanoparticles, thereby greatly improving the atomic utilization rate of platinum group metals. Moreover, the water electrolysis catalyst prepared by the method of the present application combines the high conductivity of graphene, M x S yDue to the abundant active sites and the intrinsic high catalytic activity of platinum group metals, the water electrolysis catalyst can still maintain efficient catalytic performance and electron transport capability even at low platinum group metal loading.

[0029] In summary, this application constructs M on a graphene substrate. x S y The composite structure, assisted by plasma surface modification, creates an environment rich in active defect sites; and then through magnetron sputtering and / or chemical vapor deposition, the precise anchoring of single atoms of platinum group metals can be achieved. The method of this application can not only significantly reduce the loading of platinum group metals, but also optimize the charge transfer path at the structural level, and improve the intrinsic activity and stability of the water electrolysis catalyst.

[0030] In addition, compared with the traditional method of establishing a strong metal-carrier interaction through calcination to achieve single-atom dispersion, the single-atom loading process in the method of the present application does not involve high-temperature calcination, the process is simple, the preparation cycle is short, and it is conducive to large-scale production.

[0031] In a preferred embodiment, the sulfur precursor includes one or more of thiourea, sodium sulfide and potassium sulfide, and the molar concentration is 0.01-10 mol / L; and / or, the M-containing precursor includes anions and cations, the anions include one or more of chloride ions, sulfate ions, acetate ions and acetylacetonate ions, and the cations include M ions, and the molar concentration of the M-containing precursor is 0.01-10 mol / L; and / or, the structure directing agent includes one or more of sodium fluoride, barium chloride, ethylenediamine and cystine, and the molar concentration is 0.001-0.1 mol / L, and the pH of the first solution is controlled to be 6-8 by using the structure directing agent; and / or, the alcohol includes one or more of methanol, ethanol, ethylene glycol, glycerol and isopropanol, and the volume ratio of water to alcohol is (0.1-10):1. Under the above conditions, graphene and M can be made to form a 3D-type graphene film. x S y It can be more fully and evenly compounded, and at the same time further optimize the crystallinity and dispersibility of the electrolytic water catalyst to form a highly active M x S y @rGO heterojunction.

[0032] In a preferred embodiment, the solid-liquid ratio of graphene oxide to the first solution is (1-50) mg:100 mL. The above content of graphene oxide can more effectively adjust the structure and properties of the two-dimensional composite material, promote the uniform deposition of the M-containing precursor and the sulfur precursor on the graphene surface, thereby further significantly improving the catalytic efficiency of the hydrogen evolution reaction and reducing the overpotential.

[0033] In order to further promote the uniform dispersion of the first solution and graphene oxide and enhance the contact and reaction efficiency between the materials, in a preferred embodiment, in step S1, mixing includes ultrasound and / or stirring, and the mixing temperature is 10 to 30°C; preferably, the frequency of ultrasound is 20 to 40 kW, and the time is 0.5 to 4 h; preferably, the stirring speed is 100 to 400 rpm, and the time is 1 to 12 h.

[0034] In a preferred embodiment, the temperature of the hydrothermal reaction is 160 to 200 ° C, and the time is 2 to 10 hours. Under the above conditions, the M-containing precursor and the sulfur precursor can form sulfides by chemical bonding. At the same time, graphene oxide can be converted into graphene under the action of a reducing agent. Under the synergistic effect of the two, a 2D / 2D heterojunction is constructed, which can significantly enhance the electron transfer path and improve the conductivity and reactivity of the electrolytic water catalyst. Moreover, within the above range, the material structure agglomeration caused by high-temperature hydrothermal can be more effectively avoided, which is more conducive to ensuring the loading efficiency and stability of the single-atom catalyst, and providing a precursor material with a complete structure and rich active sites for subsequent plasma treatment and vapor deposition.

[0035] In order to further improve the purity of the electrolytic water catalyst and enhance its structural integrity and electron transport capacity, in a preferred embodiment, step S1 also includes the step of washing the first intermediate catalyst 2 to 6 times and centrifuging it 2 to 6 times alternately, and then drying it; preferably, the centrifugal speed is 5000 to 10000 rpm, and the time is 0.5 to 5 hours; preferably, water, ethanol, carbon disulfide, acetone and water are used for washing in sequence; preferably, the drying temperature is 30 to 100 ° C, and the time is 0.5 to 24 hours. For example, the first intermediate catalyst is first washed with water for the first time and centrifuged for the first time, then washed with ethanol for the second time and centrifuged for the second time, then washed with carbon disulfide for the third time and centrifuged for the third time, then washed with acetone for the fourth time and centrifuged for the fourth time, then washed with water for the fifth time and centrifuged for the fifth time, and finally dried.

[0036] In a preferred embodiment, in step S2, in the second solution, the content of the first intermediate catalyst is 10 to 100 mg / mL; under this condition, the dispersion of the electrolytic water catalyst in the subsequent plasma surface treatment process can be further improved, the efficient generation of surface defect sites can be promoted, and more abundant sites can be provided for the anchoring of single-atom platinum group metals. In a preferred embodiment, the second solution also includes one or more of methanol, ethanol, ethylene glycol, glycerol and isopropanol. Under the above conditions, not only can the dispersibility of the first intermediate catalyst be further improved, but also the electronic structure of the material can be further optimized and the reaction activity of the electrolytic water catalyst can be enhanced through interaction with the catalyst surface.

[0037] In a preferred embodiment, the coating comprises one or more of ultrasonic spraying, screen printing and spin coating; and / or the substrate comprises one or more of a stainless steel plate, a nickel plate, a titanium plate and a copper plate; and / or after coating, the coating density of the coating on the surface of the irradiated substrate is 0.5 to 10 mg / cm 2 , with a thickness of 0.1 to 10 μm. Under the above conditions, the binding force and dispersibility of the electrolytic water catalyst on the substrate surface can be further enhanced, which is helpful for subsequent uniform plasma etching of the catalyst.

[0038] In a preferred embodiment, in step S2, the power of plasma irradiation is 100-300W, when the atmosphere includes H2 and inert gas, the vacuum degree is 10-100Pa, the temperature is 25-50°C, and the time is 0.5-3h; preferably, the atmosphere includes H2 and inert gas, and the volume ratio of the two is 1:(25-100). Under the above conditions, it is not only more conducive to stabilizing the processing environment, but also can further promote the precise anchoring of single-atom platinum group metals, thereby being more conducive to significantly improving the activity and stability of the electrolytic water catalyst.

[0039] In order to provide a more stable anchoring point and further improve the reaction activity and electron transfer rate of the water electrolysis catalyst, in a preferred embodiment, the number of vacancy defects in the second intermediate catalyst is 5 to 15 / nm 2 .

[0040] In a preferred embodiment, in step S3, the magnetron sputtering method includes: placing the irradiated substrate in a vacuum chamber, applying electric and magnetic fields in a vacuum environment to ionize the sputtering gas into gas ions, and using the gas ions to impact the cathode target so that the atoms of the cathode target escape and sputter on the surface of the irradiated substrate to load the platinum group metal, wherein the cathode target is selected from ruthenium, rhodium, palladium, osmium, iridium or platinum, the distance between the cathode target and the irradiated substrate is 2 to 20 cm, the sputtering power is 10 to 100 W, the sputtering time is 5 to 30 min, the temperature of the irradiated substrate is 20 to 50 ° C, the sputtering gas is argon or helium, and the gas flow rate is 20 to 100 mL / min. Under the above conditions, it is more conducive to ensuring the uniform distribution and high loading of single atoms, avoiding the agglomeration of platinum group metals, and maintaining the atomic-level dispersion state.

[0041] In a preferred embodiment, the vapor deposition method includes: heating and vaporizing a platinum group metal precursor salt and sending it into a reaction chamber through a carrier gas, wherein the platinum group metal precursor salt releases atoms on the surface of the irradiated substrate, and the platinum group metal is deposited on the surface of the irradiated substrate, wherein the carrier gas includes one or more of oxygen, hydrogen, argon and helium, and the platinum group metal precursor includes one or more of ruthenium, rhodium, palladium, osmium, iridium and platinum. The acetylacetonate salt, the vaporization temperature of the platinum group metal precursor is 150-200°C, the temperature of the irradiated substrate is 200-300°C, the pressure is 1-100kPa, and the deposition time is 5-120min. Under the above conditions, the density and stability of the active sites of the electrolytic water catalyst can be further enhanced.

[0042] In another typical embodiment of the present invention, a water electrolysis catalyst is provided, which is obtained by the above preparation method.

[0043] As mentioned above, in the preparation method of the present application, plasma treatment technology is used to treat M x S y The introduction of high-density defects on the surface of @GO can provide stable anchoring points for single atoms of platinum group metals, significantly enhancing the activity of water electrolysis catalysts; the precise application of magnetron sputtering and vapor deposition technology is not only conducive to ensuring the uniform deposition of single atoms of platinum group metals, but also can optimize their spatial selectivity, avoid the waste of precious metal elements, and significantly reduce costs. x S y @The synergistic effect of GO and PGM (platinum group metal) single atoms forms a heterojunction catalyst with high catalytic activity, stable performance and economy.

[0044] In a preferred embodiment, in the water electrolysis catalyst, the loading amount of the platinum group metal is 0.01-2 wt %, the weight percentage of graphene is 10-20 wt %, and the M x S y The weight percentage is 78-88wt%; and / or, the platinum group metal in the water electrolysis catalyst exists in the form of a single atom, and / or, M x S y The thickness is 1 to 5 nm.

[0045] In another typical embodiment of the present invention, the application of the above-mentioned electrolytic water catalyst in the field of electrolytic water is also provided. As mentioned above, the electrolytic water catalyst of the present application has high catalytic activity, and stable performance, economy, when it is used in the field of electrolytic water, the overpotential is low, the hydrogen evolution efficiency is high, and long-term stable operation can be achieved, and the alkaline water electrolysis hydrogen production process can also be optimized, and the technical difficulties of insufficient catalyst active sites and low electron transfer efficiency can be overcome, and key material support can be provided for low-cost, high-performance clean energy preparation technology.

[0046] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0047] Example 1

[0048] The schematic diagram of the preparation process of water electrolysis catalyst is shown in Figure 1 .

[0049] Specifically, the preparation method of the water electrolysis catalyst comprises the following steps:

[0050] Step S1, preparing 100mL of a first mixed solution consisting of 0.1mol / L M-containing precursor (nickel chloride), 0.2mol / L sulfur precursor (thiourea), 0.02mol / L structure directing agent (ethylenediamine), water and ethylene glycol (water-to-alcohol ratio of 1:1), with a pH value of about 6; adding 25mg of rGO to the first solution, ultrasonically dispersing for 30min, and controlling the temperature at 25°C to mix; then, transferring the mixed solution to a 150mL polytetrafluoroethylene-lined hydrothermal autoclave, with the solution accounting for 66.7%, hydrothermally heated at 180°C for 2h, and then centrifuged at 5000rmp for 0.5h to separate the first intermediate catalyst, and then using water, ethanol, carbon disulfide, acetone, and water as cleaning agents in sequence to perform 5 dispersion-centrifugal separation operations, dispersing using ultrasonic dispersion method, centrifugal speed of 5000rpm, time of 0.5h, and finally freeze drying for 12h.

[0051] Step S2, dispersing the first intermediate catalyst in an ethanol solution to obtain a second solution, wherein the content of the first intermediate catalyst is 25 mg / mL, and then uniformly coating the second solution on a substrate (nickel plate) by ultrasonic spraying, and controlling the coating density of the coating to be 2 mg / cm 2 , with a thickness of 1 μm; then the substrate is placed in a vacuum chamber of a plasma surface treatment equipment, evacuated to a vacuum degree of 10 Pa, the plasma power is 250 W, the atmosphere is a mixture of H2 and Ar, the volume ratio of the two is 1:50, the treatment time is 2 h, the temperature is 30 ° C, and a second intermediate catalyst is obtained on the surface of the substrate.

[0052] Step S3, placing the substrate including the second intermediate catalyst in a vacuum chamber of a magnetron sputtering method, applying an electric field and a magnetic field in a vacuum environment to ionize the sputtering gas into gas ions, using the gas ions to impact the cathode target, so that the atoms of the cathode target escape and sputter on the surface of the irradiated substrate, the distance between the target and the substrate is 10 cm, the sputtering power is 45 W, the sputtering time is 20 min, the temperature of the sputtering substrate is 25 ° C, the sputtering gas is argon, the gas flow rate is 50 mL / min, to load the platinum group metal, wherein the cathode target is a metal platinum rod; using a clean polytetrafluoroethylene brush, the electrolytic water catalyst is peeled off from the substrate to obtain the electrolytic water catalyst (Pt SAC -NiS x @GO).

[0053] The microscopic morphology of the prepared water electrolysis catalyst is shown in Figure 2 , Figure 3 , from which an obvious two-dimensional lamellar structure can be observed.

[0054] Example 2

[0055] The only difference from Example 1 is:

[0056] The platinum group metal precursor salt is heated, vaporized and sent into the reaction chamber through the carrier gas by vacuum vapor deposition. The platinum group metal precursor salt releases atoms on the surface of the irradiated substrate, so that the platinum group metal is deposited on the surface of the irradiated substrate. The carrier gas is argon with a pressure of 1×10 4 Pa, replaced the magnetron sputtering method, in which the organic precursor was selected as platinum acetylacetonate, the precursor vaporization temperature was 175°C, the deposition substrate temperature was 250°C, and the deposition time was 60 min to obtain the electrolytic water catalyst (Pt SAC -NiS x @GO-g).

[0057] Example 3

[0058] The only difference from Example 1 is that in step S1, the raw materials and preparation process parameters of the first intermediate catalyst are different. Specifically, in step S1, 100 mL of a solvent system is taken, wherein the M precursor is manganese sulfate with a concentration of 0.01 mol / L, the sulfur precursor is thiourea with a concentration of 0.1 mol / L, the structure directing agent is barium chloride with a concentration of 0.001 mol / L, the volume ratio of water to ethanol is 10:1, the pH value is adjusted to 6, and graphene oxide is added to a concentration of 0.01 mg / mL, and the reaction mixture is stirred at a temperature of 10 °C by ultrasonication. ℃ and mixed for 20 minutes, then transferred to a 250mL polytetrafluoroethylene-lined hydrothermal autoclave with a solution ratio of 40%, and hydrothermally reacted at a temperature of 160℃ for 1 hour, followed by centrifugation at a speed of 5000rpm for 0.5h to separate the first intermediate catalyst, and then used water, ethanol, carbon disulfide, acetone, and water as cleaning agents for 5 dispersion-centrifugation operations. Ultrasonic dispersion was used for dispersion, the centrifugal speed was 5000rpm, the time was 0.5h, and freeze-drying was used for 24h.

[0059] Example 4

[0060] The only difference from Example 1 is:

[0061] In step S1, the raw materials and preparation process parameters of the first intermediate catalyst are different. Specifically, in step S1, 100 mL of a solvent system is configured, containing an M precursor with a concentration of 10 mol / L copper chloride, a sulfur precursor with a concentration of 10 mol / L sodium sulfide, a structure directing agent with a sodium fluoride concentration of 0.1 mol / L, a volume ratio of water to propylene glycol of 1:10, a pH value of 8, and an amount of graphene oxide added of 0.5 mg / mL. Ultrasonic mixing is performed at a temperature of 30°C for 1 h, and then in a 150 mL polypropylene-lined hydrothermal autoclave, the solution accounts for 66.7%, and the reaction is performed at 200°C for 10 h, followed by centrifugation at 5000 rpm for 0.5 h to separate the first intermediate catalyst, and then water, ethanol, carbon disulfide, acetone, and water are used as cleaning agents in sequence to perform 5 dispersion-centrifugal separation operations. The dispersion adopts an ultrasonic dispersion method, the centrifugal speed is 5000 rpm, the time is 0.5 h, and then freeze-drying is adopted for a drying time of 24 h.

[0062] Example 5

[0063] The only difference from Example 1 is:

[0064] In step S2, the process parameters of coating and plasma treatment are different. Specifically, the first intermediate catalyst is dispersed in the second solution (the content of the first intermediate catalyst in the second solution is 10 mg / mL), and then coated on the nickel plate substrate. The coating density of the coating is 0.5 mg / cm 2, thickness is 0.1μm; plasma treatment adopts power 100W, pure Ar atmosphere, vacuum degree 10Pa, temperature 25℃, and treatment time 3h.

[0065] Example 6

[0066] The only difference from Example 1 is:

[0067] In step S2, the process parameters of coating and plasma treatment are different. Specifically, the first intermediate catalyst is dispersed in the second solution (the content of the first intermediate catalyst in the second solution is 100 mg / mL), and then coated on the surface of the titanium plate. The coating density of the coating is 10 mg / cm 2 , thickness is 10μm; the plasma treatment adopts a power of 300W, a H2:Ar mixed gas atmosphere (volume ratio 1:50), a vacuum degree of 100Pa, a temperature of 50℃, and a treatment time of 0.5h.

[0068] Example 7

[0069] The only difference from Example 1 is:

[0070] In step S3, in the magnetron sputtering method, the cathode target composition is different. Specifically, the cathode target is palladium, the distance between the target and the substrate is 12 cm, the sputtering power is 50 W, the sputtering time is 25 min, the sputtering gas is argon, the gas flow rate is 40 mL / min, and the sputtering substrate temperature is 45 ° C.

[0071] Example 8

[0072] The only difference from Example 1 is:

[0073] In step S3, in the magnetron sputtering method, the cathode target composition is different. Specifically, the cathode target is ruthenium, the distance between the target and the substrate is 18 cm, the sputtering power is 40 W, the sputtering time is 30 min, the sputtering gas is argon, the gas flow rate is 45 mL / min, and the sputtering substrate temperature is 35 ° C.

[0074] Example 9

[0075] The only difference from Example 2 is that:

[0076] In step S3, vacuum vapor deposition was used, the precursor component was osmium acetylacetonate, the carrier gas was helium, and the pressure was 1×10 5 Pa, precursor vaporization temperature 185 °C, deposition substrate temperature 275 °C.

[0077] Example 10

[0078] The only difference from Example 2 is that:

[0079] In step S3, vacuum vapor deposition was used, the precursor component was iridium acetylacetonate, the carrier gas was argon, and the pressure was 5×10 4 Pa, precursor vaporization temperature 195 °C, deposition substrate temperature 280 °C.

[0080] Comparative Example 1

[0081] The only difference from Example 1 is that no plasma treatment is performed.

[0082] Comparative Example 2

[0083] The only difference from Example 1 is that the magnetron sputtering method is replaced by the traditional solution impregnation calcination method for loading the precious metal Pt. Specifically, 1 g of the second intermediate catalyst treated with plasma is dispersed in 50 mL of deionized water, followed by adding 0.0266 g of chloroplatinic acid hexahydrate, stirring and heating in an 80°C water bath to evaporate the impregnation solution, then drying in a 60°C oven overnight, and then calcining at 350°C in an argon atmosphere for 2 h.

[0084] Comparative Example 3

[0085] The only difference from Example 1 is that the raw material does not include the first solution, and the obtained water electrolysis catalyst does not include M x S y .

[0086] Comparative Example 4

[0087] The only difference from Example 1 is that the raw material does not include graphene oxide, and the water electrolysis catalyst does not include graphene.

[0088] Comparative Example 5

[0089] The cathode catalyst for water electrolysis is 40wt% Pt / C (model HiSPEC4000), and the anode catalyst is IrO x (Model I811643), AEM is FAA-3-50, and the loading of cathode and anode catalyst on AEM is 2 mg / cm 2 .

[0090] The characteristic parameters and performance test results of the water electrolysis catalysts prepared in the above examples and comparative examples are shown in Table 1.

[0091] Test method:

[0092] Platinum group metal loading: Tested in accordance with GB / T 30902-2014: Determination of impurity elements in inorganic chemical products by inductively coupled plasma optical emission spectrometry (ICP-OES).

[0093] Hydrogen evolution performance test of water electrolysis catalyst: 10 mg of the prepared water electrolysis catalyst was added to 4 mL of a mixed solvent of water and isopropanol, and ultrasonicated to form a uniform catalyst ink. Then a certain amount of ink was evenly dropped on a 5 mm glassy carbon rotating disk electrode as a working electrode for testing. The loading of the water electrolysis catalyst was 0.255 mg / cm 2 The disc speed in the test was 2500rpm. The water electrolysis catalyst was used for hydrogen evolution reaction in alkaline electrolyte. In the three-electrode test system, platinum wire was the counter electrode, mercury / mercuric oxide electrode was the reference electrode, and 1mol / L potassium hydroxide was selected as the electrolyte in the test system. The electrochemical data of the water electrolysis catalyst were tested by linear voltammetric scanning and AC impedance method. The linear voltammetric scanning rate was 5mV / s, and the test electrode was tested at 20mA / cm 2 The overpotential of hydrogen evolution under the current density; the test potential of AC impedance is -0.1V (vs.RHE), the AC amplitude is 10mV, and the frequency range is 10 6 ~10 -1 Hz, and the charge transfer resistance was obtained by fitting the equivalent circuit of the impedance spectrum.

[0094] The alkaline water electrolysis hydrogen production performance test of the water electrolysis catalyst: The water electrolysis catalyst was ultrasonically sprayed on the AEM membrane (model FAA-3-50) as the cathode catalyst, and commercial IrO x The water electrolysis catalyst (model I811643) was used as an anode catalyst to prepare a CCM membrane electrode.

[0095] Specifically, 225 mg of electrolytic water catalyst was taken to prepare a total volume of 15 mL of water and isopropanol mixed spray slurry, and an anion exchange membrane ionomer solution (model Pention-S72-5wt%) was added at the same time, and a uniform first catalyst ink was formed after ultrasound; 225 mg of commercial IrO x Catalyst (model I811643), prepare a total volume of 15mL of water and isopropanol mixed spray slurry, and add anion exchange membrane ionomer dispersion (model Pention-S72-5wt%) at the same time, so that the anion exchange membrane ionomer content is 20% of the mass of the electrolytic water catalyst, and form a uniform second catalyst ink after ultrasound; use ultrasonic spraying to spray the first catalyst ink and the second catalyst ink on both sides of a commercial AEM (model FAA-3-50), respectively, with a loading of 2mg / cm 2 , and obtain the CCM membrane electrode, which is placed in a 1 mol / L NaOH solution and left to activate for 24 hours.

[0096] The CCM membrane electrode, anode gas diffusion layer (nickel felt) and cathode diffusion layer (nickel felt) were assembled and the single cell performance test was carried out. During the test, the electrode clamps of the electrochemical workstation were clamped on the positive and negative electrodes of the electrolyzer, and 1M KOH solution was circulated at a flow rate of 100ml / min. The heating device was turned on and the temperature was set to 60℃. The samples reached 2A / cm in the water electrolysis test. 2 The chamber voltage at the current density represents the hydrogen production voltage value of a single electrolysis unit when a certain current density is reached. Therefore, the lower the value, the lower the energy consumption under the current density and the higher the economy of the hydrogen production reaction.

[0097] Table 1

[0098]

[0099] Compared with Example 1, the catalyst in Example 2 also has high activity after the single-atom platinum loading is carried out by vapor deposition method, which proves the importance of plasma etching defects to the synthesis of single-atom catalysts.

[0100] Examples 3 and 4 show that the hydrothermal conditions affect the yield, micromorphology, degree of agglomeration, size, specific surface area of ​​the first intermediate catalyst, and the degree of reduction of graphene oxide, which in turn affects the deposition process and dispersion of single-atom metals, and ultimately affects the charge conduction performance of the catalyst.

[0101] Example 5 shows that the plasma etching power affects the defects generated on the surface of the first intermediate catalyst, thereby affecting the deposition process of Pt.

[0102] Example 6 shows that the coating density, thickness and plasma treatment power of the coating affect the degree of etching of the catalyst on the coating surface and the internal catalyst, thereby affecting the number of defects formed and further affecting the uniformity of Pt deposition.

[0103] In Examples 7 and 8, the magnetron sputtering target was replaced and the process parameters were adjusted to prepare single-atom palladium and single-atom ruthenium catalysts, which proved that the synthesis method of the present invention is universal for the selection of precious metal types.

[0104] In Examples 9 and 10, the vapor deposition precursor was replaced and the process parameters were adjusted to prepare single-atom osmium and single-atom iridium catalysts, which proved that the synthesis method of the present invention is universal for the selection of precious metal types.

[0105] Compared with Example 1, Comparative Example 1 does not perform plasma treatment, and the surface of the second intermediate catalyst fails to produce defects, and cannot provide anchoring points for the deposition of Pt, so Pt fails to form a single-atom-level dispersion characteristic; Comparative Example 2 uses a traditional impregnation calcination method to load Pt, and can form highly dispersed Pt on the surface of the second intermediate catalyst, but does not reach the single-atom-level dispersion level; the electrolytic water catalyst in Comparative Example 3 does not include M x S y , Pt fails to produce strong electronic interaction with metal sulfides, and the catalytic performance is low; the water electrolysis catalyst in Comparative Example 4 does not include graphene, resulting in a serious decrease in the conductivity of the catalyst, affecting the performance of hydrogen production by water electrolysis; the commercial Pt / C in Comparative Example 5 has better catalytic performance, but the Pt loading is as high as 40wt%, and the economic efficiency is poor.

[0106] As can be seen from the above, the present invention constructs M on a graphene substrate. x S y The composite structure, assisted by plasma surface modification, creates an environment rich in active defect sites; and then through magnetron sputtering and / or chemical vapor deposition, the precise anchoring of single atoms of platinum group metals can be achieved. The method of the present invention can not only significantly reduce the loading of platinum group metals, but also optimize the charge transfer path at the structural level, thereby improving the intrinsic activity and stability of the water electrolysis catalyst.

[0107] In addition, compared with the traditional method of establishing a strong metal-carrier interaction through calcination to achieve single-atom dispersion, the single-atom loading process in the method of the present invention does not involve high-temperature calcination, the process is simple, the preparation cycle is short, and it is conducive to large-scale production.

[0108] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a water electrolysis catalyst, characterized in that: The water electrolysis catalyst comprises graphene, M x S y and a single atom of a platinum group metal, the preparation method comprising the following steps: Step S1, mixing a sulfur precursor, an M-containing precursor, a structure directing agent, water and an alcohol to obtain a first solution, adding graphene oxide to the first solution, performing a hydrothermal reaction, and obtaining a first intermediate catalyst; Step S2, coating a second solution including the first intermediate catalyst on a substrate surface, and performing plasma irradiation to generate a second intermediate catalyst on the substrate surface, thereby obtaining an irradiated substrate; Step S3, treating the irradiated substrate by magnetron sputtering and / or chemical vapor deposition to load the platinum group metal and obtain the water electrolysis catalyst on the surface of the substrate; The M x S y wherein M includes one or more of Ni, Zn, Mo and Co, 1≤x≤2, 1≤y≤3; The platinum group metal includes one or more of ruthenium, rhodium, palladium, osmium, iridium and platinum.

2. The preparation method according to claim 1, characterized in that: In the step S1, The sulfur precursor includes one or more of thiourea, sodium sulfide and potassium sulfide, with a molar concentration of 0.01 to 10 mol / L; and / or, The M-containing precursor includes anions and cations, the anions include one or more of chloride ions, sulfate ions, acetate ions and acetylacetonate ions, the cations include M ions, and the molar concentration of the M-containing precursor is 0.01 to 10 mol / L; and / or, The structure directing agent comprises one or more of sodium fluoride, barium chloride, ethylenediamine and cystine, with a molar concentration of 0.001 to 0.1 mol / L, and the pH of the first solution is controlled to be 6 to 8 by using the structure directing agent; and / or, The alcohol includes one or more of methanol, ethanol, ethylene glycol, glycerol and isopropanol, and the volume ratio of water to the alcohol is (0.1-10):1; and / or, The solid-to-liquid ratio of the graphene oxide to the first solution is (1-50) mg:100 mL.

3. The preparation method according to claim 1 or 2, characterized in that: In the step S1, The mixing includes ultrasound and / or stirring, the mixing temperature is 10-30°C; preferably, the frequency of the ultrasound is 20-40kW, the time is 0.5-4h; preferably, the speed of the stirring is 100-400rpm, the time is 1-12h; and / or, The temperature of the hydrothermal reaction is 160-200° C. and the time is 2-10 hours; and / or, The step S1 also includes the step of washing the first intermediate catalyst alternately for 2 to 6 times and centrifuging it for 2 to 6 times, and then drying it; preferably, water, ethanol, carbon disulfide, acetone and water are used in sequence for the washing; preferably, the centrifugal speed is 5000 to 10000 rpm, and the time is 0.5 to 5 hours; preferably, the drying temperature is 30 to 100°C, and the time is 0.5 to 24 hours.

4. The preparation method according to any one of claims 1 to 3, characterized in that In the step S2, In the second solution, the content of the first intermediate catalyst is 10 to 100 mg / mL; and / or, The second solution further comprises one or more of methanol, ethanol, ethylene glycol, glycerol and isopropanol; and / or, The coating comprises one or more of ultrasonic spraying, screen printing and spin coating; and / or, The substrate includes one or more of a stainless steel plate, a nickel plate, a titanium plate and a copper plate; and / or, After the coating, the coating density of the coating on the surface of the irradiated substrate is 0.5-10 mg / cm 2 , thickness is 0.1~10μm.

5. The preparation method according to any one of claims 1 to 4, characterized in that: In the step S2, The power of the plasma irradiation is 100-300W, the atmosphere includes inert gas and / or H2, the vacuum degree is 10-100Pa, the temperature is 25-50°C, and the time is 0.5-3h; Preferably, the atmosphere comprises H2 and an inert gas, and the volume ratio of the two is 1:(25-100).

6. The preparation method according to any one of claims 1 to 5, characterized in that The number of vacancy defects in the second intermediate catalyst is 5 to 15 per nm. 2 .

7. The preparation method according to any one of claims 1 to 6, characterized in that In the step S3, The magnetron sputtering method comprises: placing the irradiated substrate in a vacuum chamber, applying an electric field and a magnetic field in a vacuum environment to ionize the sputtering gas into gas ions, using the gas ions to impact a cathode target, so that atoms of the cathode target escape and sputter on the surface of the irradiated substrate to load the platinum group metal, wherein the cathode target is selected from ruthenium, rhodium, palladium, osmium, iridium or platinum, the distance between the cathode target and the irradiated substrate is 2 to 20 cm, the sputtering power is 10 to 100 W, the sputtering time is 5 to 30 min, the temperature of the irradiated substrate is 20 to 50° C., the sputtering gas is argon or helium, and the gas flow rate is 20 to 100 mL / min; and / or, The vapor deposition method comprises: heating and vaporizing a platinum group metal precursor salt and delivering it into a reaction chamber through a carrier gas, wherein the platinum group metal precursor salt releases atoms on the surface of the irradiated substrate to deposit the platinum group metal on the surface of the irradiated substrate, wherein the carrier gas comprises one or more of oxygen, hydrogen, argon and helium, the platinum group metal precursor comprises one or more of acetylacetonate of ruthenium, rhodium, palladium, osmium, iridium and platinum, the vaporization temperature of the platinum group metal precursor is 150-200° C., the temperature of the irradiated substrate is 200-300° C., the pressure is 1-100 kPa, and the deposition time is 5-120 min.

8. A water electrolysis catalyst, characterized in that: The method is obtained by the preparation method according to any one of claims 1 to 7.

9. The water electrolysis catalyst according to claim 8, characterized in that: In the water electrolysis catalyst, the loading amount of the platinum group metal is 0.01-2wt%, the content of graphene is 10-20wt%, and the content of M x S y The content of is 78-88wt%; and / or, In the water electrolysis catalyst, the platinum group metal exists in the form of a single atom.

10. Use of the water electrolysis catalyst according to claim 8 or 9 in the field of water electrolysis.

Citation Information

Cited By

  • Nickel-cobalt catalyst for AEM water electrolysis hydrogen production, preparation method of catalytic electrode and application of nickel-cobalt catalyst and catalytic electrode

    CN120575223A